Post-fire behaviour and capacity of high strength concrete-filled high strength steel tube (HCFHST) stub columns under combined compression and bending - Zhong, Yukai (2022)
The post-fire behaviour and capacity of high strength concrete-filled high strength steel tube (HCFHST) stub columns under combined compression and bending have been investigated through testing and numerical modelling and reported in this paper. Eccentric compression tests were conducted on eight square HCFHST stub column specimens after exposure to the ISO-834 standard fire for 15 min, 30 min, 45 min and 80 min and two reference specimens at ambient temperature. The test results, including the load–deformation response at each load stage as well as the confinement effect, the ductility index, the evolution of the neutral axis, the effect of heating duration and the effect of initial loading eccentricity, were discussed. Numerical simulations were then carried out, where thermal and mechanical finite element models were developed and validated against the test results and afterwards used to perform parametric studies to generate further numerical data over a wide range of cross-section dimensions and loading combinations. Given that there are no established design codes for composite structures after exposure to fire, the relevant ambient temperature design rules were evaluated, using post-fire material properties, for their applicability to post-fire HCFHST stub columns under combined compression and bending, based on the test and numerical data. The evaluation results revealed that the European code, American specification and Australian/New Zealand standard result in relatively accurate and consistent post-fire residual resistance predictions.